Defect-correlated fatigue assessment of A356-T6 aluminum cast alloy using computed tomography based Kitagawa-Takahashi diagrams. (March 2018) - Tenkamp, Jochen; Koch, Alexander; Knorre, Stephan; Krupp, Ulrich; Michels, Wilhelm; Walther, Frank
Highlights: Influence of porosity characteristics on mechanical behavior of A356-T6. Shrinkage and gas porosity was separated using micro-computed tomography. Fatigue behavior and fatigue crack propagation behavior of A356-T6. Fatigue limit was correlated with porosity using Kitagawa-Takahashi diagrams. S-N curve was evaluated using Paris law and characteristic initial pore size. Abstract: Modern aluminum cast alloys are promising candidates for highly loaded lightweight components due to their good strength-to-weight ratio. To enable a safe design of aluminum cast components, the microstructure characteristics, e.g. porosity, secondary dendrite arm spacing and Si eutectic morphology, have to be taken into account. This study deals with the influence of different porosity characteristics on the fatigue behavior of A356-T6 aluminum cast alloy. For this purpose, cyclic deformation tests have been carried out to study fatigue damage and fatigue crack growth in the high cycle fatigue (HCF) regime up to 10 7 cycles. The porosity of each batch was quantified using micro-computed tomography. Results show that large porosity dominates the HCF fatigue behavior. The relationship between porosity characteristics and the fatigue limit as well as S-N curve was assessed by Kitagawa-Takahashi diagrams and a fracture mechanic approach.